Signal Management: Updated Requirements of the EAEU Good Pharmacovigilance Practice - A. V. Matveev; A. E. Krasheninnikov; A. Yu. Zelinskaya (Безопасность и риск фармакотерапии)
The Rules of Good Pharmacovigilance Practice of the Eurasian Economic Union (EAEU GVP Guideline) came into force in the EAEU Member States in 2017. Over the next 5 years, marketing authorisation holders and competent authorities managed to build effective pharmacovigilance systems. The current version of the EAEU GVP Guideline was published in May 2022 and enacted on 6 December 2022. Amongst the critical pharmacovigilance processes, a special place is reserved to the process of signal management.The aim of the study was to analyse the new content of the EAEU GVP Guideline related to signal management.The authors reviewed the amendments introduced to the module of the EAEU GVP Guideline on signal management. This article is the first scholarly publication in the Russian language on the updated signal management process. The key changes include a detailed consideration of terminology issues, signal validation and prioritisation processes, notifying competent authorities of signal evaluation results, managing emerging safety issues, and functions of new automated systems: an integrated database of adverse drug reactions and a system for tracking safety issues.